1940
DOI: 10.1063/1.1750586
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of Solution of Metals in Acids as a Function of Overvoltage II. The Solution of Cadmium in Sulfuric Acid

Abstract: Articles you may be interested inBinary nucleation in acid-water systems. II. Sulfuric acid-water and a comparison with methanesulfonic acid-water J. Chem. Phys. 94, 6842 (1991);The rate of solution of cadmium in sulfuric acid has been measured as a function of the hydrogen overvoltage at the electrode surface. The rate was found to be constant at a given potential, independent of the concentration of sulfuric acid used. The rate increases with the electrode potential in accordance with ~he theory of Kimball. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
8
0

Year Published

1943
1943
1977
1977

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 6 publications
3
8
0
Order By: Relevance
“…Repeat tests with different electrodes (shown by the various points at each potential) show that this difference is statistically significant. This result is parallel to that found for Cu in dilute H2SO~ (11) but is unexpected in light of various other mixed potential systems (5)(6)(7)(8)(9). Other trends from Fig.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Repeat tests with different electrodes (shown by the various points at each potential) show that this difference is statistically significant. This result is parallel to that found for Cu in dilute H2SO~ (11) but is unexpected in light of various other mixed potential systems (5)(6)(7)(8)(9). Other trends from Fig.…”
Section: Resultssupporting
confidence: 78%
“…In order for this superposition approach to function it is necessary that the rate and kinetics of each partial reaction be independent of the other partial reaction(s) at a given potential. This independence of partial processes has been shown for several combinations of reductant (metals or hydrogen) and oxidant (5)(6)(7)(8)(9), and consequently would appear to be quite general. However, independence of the partial processes is not a necessary criteria for charge and mass balance across the electrode-solution interface, as suggested in some previous work (10,12).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…
The problem of the dissolution of cadmium in various aqueous media has been investigated intermittently over the past two decades (2,3,4,5,7,8,9,10,11,12,13,14 and 15), the chief work being that carried out by Centnerszwer and coworkers. The published data appear to be at variance in several places, and in some cases are of doubtful validity.
…”
mentioning
confidence: 99%
“…Kimball and Glassner (12), when investigating the rate of solution of cadmium in sulfuric acid, found that the rate could best be expressed by a zero-order equation, and showed that this should be the order on a theoretical basis.…”
mentioning
confidence: 99%